Pengaruh Product Quality Dan Brand Image Terhadap Repurchase Intention Yang Dimediasi Oleh Brand Trust Pada Produk Susu UHT Ultra Milk Di Kota Cimahi - Ferry Ruhananta; Abdul Ahmad Hafidh Nurmansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to identify and analyze the direct influence of product quality and brand image on repurchase intention, with brand trust as a mediating variable, in the case of UHT Ultra Milk products in Cimahi City. This research employs a quantitative method with a sample of 160 respondents who consume UHT Ultra Milk products in Cimahi. The data were analyzed using multiple linear regression tests with the assistance of IBM SPSS Statistics 27. The results show that product quality and brand image have a direct influence on repurchase intention for UHT Ultra Milk products in Cimahi. Furthermore, brand trust was found to partially mediate the relationship between product quality and brand image with repurchase intention. The implications of this study suggest that companies need to focus on improving product quality and building a positive brand image, as well as fostering brand trust in order to encourage consumers’ repurchase intention.